2017
DOI: 10.1186/s12984-017-0316-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous visual feedback during sitting balance training in chronic stroke survivors

Abstract: BackgroundPostural control deficits are common in stroke survivors and often the rehabilitation programs include balance training based on visual feedback to improve the control of body position or of the voluntary shift of body weight in space. In the present work, a group of chronic stroke survivors, while sitting on a force plate, exercised the ability to control their Center of Pressure with a training based on continuous visual feedback. The goal of this study was to test if and to what extent chronic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 65 publications
(71 reference statements)
3
25
0
Order By: Relevance
“…Overall, it is observed that majority of the parameters showed statistically significant variations between different trial conditions. This indicates that, similar previous works [21][22][23][24], the seat mode and visual status both have a strong relationship with the quality of seated postural control. This is in line with our first hypothesis that difficulty of the task of seated postural control is affected by the variation in seat and visual modes.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Overall, it is observed that majority of the parameters showed statistically significant variations between different trial conditions. This indicates that, similar previous works [21][22][23][24], the seat mode and visual status both have a strong relationship with the quality of seated postural control. This is in line with our first hypothesis that difficulty of the task of seated postural control is affected by the variation in seat and visual modes.…”
Section: Discussionsupporting
confidence: 84%
“…The system is also capable of generating visual biofeedback based on the position of the user's COP. A review of previous studies on the use of COP based visual biofeedback during trunk rehabilitation on stable and unstable surfaces revealed that the inclusion of visual biofeedback improves balance related outcomes [14,[21][22][23][24][25][26]. However, these studies have mostly used stable or uncontrolled unstable platforms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gyroscopes collect angular velocity data, and can be used to compute changes in COG angular velocity and angular position. Larger values of COG angular velocity and position indicate reduced balance performance [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Stroke survivors often adapt compensatory strategies to maintain balance which leads to poor sitting ability. 3 , 4 Sitting, being a skill that is critical to independent living, is one of the useful prognostic indicators of functional outcome for stroke population. Re-establishment of control in sitting for function is an important early goal in stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%